Implementasi Outing Class Dalam Pembelajaran Bahasa Arab Pada Siswa Kelas V Sd Sa’adatul Islam Jambean Untuk Menunjang Minat Dalam Belajar Bahasa Arab - Susilaningsih, Prihati (DAS Institute, 2024)
This Study aims to: 1) To determine the application of outing classes in Arabic language learning for fifth grade students at SD Sa'adatul Islam Jambean. 2) Knowing the teaching methods and approaches used in implementing outing classes in Arabic language learning for fifth grade students at SD Sa'adatul Islam Jambean. 3) Knowing the obstacles and supporters that support interest in learning Arabic for teachers and students of class V at SD Sa'adatul Islam Jambean.Using a Qualitative Field Research approach, researcher acts as an observer. The data collection techniques use observation sheets, interview sheets, and documentation. The subjects of this research were fifth grade students at SD Sa'adatul Islam Jambean.The research results show that: 1) Implementation of the outing class program begins with planning activities and providing materials before starting the implementation of outing class activities. 2) The learning method used is a combination of outing classes and learning methods with games which have the final result of increasing students' understanding of Arabic language material. 3) The supporting factors that are the benchmark for the success of the activity are the creativity and active role of the teacher as well as the activeness of students in participating in learning with this outing class. Meanwhile, the inhibiting factor is the lack of time given to Arabic language subjects at this school.Thus, it can be concluded that Arabic language learning activities using the outing class method are supported by careful planning and preparation as well as utilization of the existing environment, indicating an increase in interest and motivation in learning Arabic among fifth grade students at Sa'adatul Islam Elementary School.